Rig for sea: Countering the deployment of Chinese ballistic missile submarines. Issue 5 (19th October 2016) - Harris, Matthew
ABSTRACT: China has made a "developmental leap" with the Type 094 ballistic missile submarine (SSBN). The anticipated commencement of strategic patrols in 2015 will provide China with a credible sea-based nuclear deterrent. This deterrent represents a growing threat to the American people and a game changer for U.S.-Chinese strategic stability. How can the United States mitigate this threat and ensure strategic stability? The deployment of the Type 094 SSBN has many similarities with the deployment of Soviet DELTA-class SSBNs in the early 1970s. This study compares the DELTA case with the Type 094 and argues for a geography-based strategy to counter the deployment of Chinese SSBNs.